Peutz-Jeghers syndrome: early clinical expression of a new STK11 gene variant. (1st October 2015) - Brito, Sara; Póvoas, Marta; Dupont, Juliette; Lopes, Ana Isabel
Abstract : Genetic heterogeneity has been recognised in Peutz-Jeghers syndrome (PJS) (over 230 STK11 gene mutations reported). We report a rare PJS phenotype with early extensive gastrointestinal (GI) presentation and a new genetic variant. The case presented as haematochezia and mucocutaneous pigmentation (the patient was 3 years of age). Endoscopy showed several polyps throughout the stomach/colon (PJ-type hamartomas); the larger polyps were resected. Small bowel imaging detected multiple jejunum/ileum small polyps. During 8 years of follow-up of this asymptomatic patient, an increasing number of diffusely distributed polyps was observed and polypectomies were performed. Subsequently, the patient failed consultations; when the patient was 13 years of age, emergency surgery was required due to small bowel intussusception (ileal polyp). A STK11 gene study identified two missense variants in heterozygous (yet unknown significance but probably pathogenic): c.854T>A (exon 6) and c.446C>T* (exon 2) (*not previously reported). We report two STK11 gene variants (one not previously described) of yet undetermined causality in a paediatric patient presenting with extensive GI involvement at a very early age, with no family medical history. Structural and functional repercussion of the newly described variants should be further investigated.